Pengalaman remaja putri dalam mengonsumsi tablet tambah darah (TTD) - Riska Subhianti Putri; Mila Sartika (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Iron deficiency anemia remains a significant health problem among adolescent girls, despite widespread implementation of iron supplementation programs in schools. Compliance with iron supplementation remains low among adolescent girls due to various physical, psychological, and social barriers. A deeper understanding of adolescent girls' experiences of iron supplementation is needed to improve the effectiveness of anemia prevention programs. Purpose: To explore the lived experiences of adolescent girls in consuming iron supplementation. Method: This qualitative research uses a descriptive phenomenological approach. The study was conducted at State Junior High School 5 North Cikarang, Bekasi Regency, West Java, from June 16 to August 15, 2025. Eight adolescent girls aged 13–15 years were selected using a purposive sampling method. Data were collected through in-depth interviews lasting 30–50 minutes and analyzed using the Colaizzi method. Results: Data analysis yielded three main themes: (1) barriers and obstacles to iron supplementation, including the unpleasant taste of the tablets, physical side effects, and indiscipline and forgetfulness; (2) positive perceptions and benefits of iron tablet consumption, including increased understanding and physical and energy changes; and (3) external support and strategies to increase adherence, involving the roles of teachers, peers, family, and adolescents' personal strategies for overcoming barriers. Conclusion: Adolescent girls' experiences of iron tablet consumption are influenced by the interaction between physical barriers, perceived benefits, and environmental support. The success of iron tablet programs depends not only on tablet distribution but also on ongoing education, social support, and implementation strategies tailored to the characteristics of adolescent girls. Suggestion: Future research is recommended to address the limitations of this study by using quantitative or mixed-method designs to examine the relationship between adherence to iron tablet consumption and objective indicators of anemia, such as hemoglobin levels, among adolescent girls. Keywords: Anemia; Adolescent Girls; Iron Supplementation. Pendahuluan: Anemia defisiensi besi masih menjadi masalah kesehatan yang signifikan pada remaja putri, meskipun program pemberian tablet tambah darah (TTD) telah dilaksanakan secara luas di sekolah. Tingkat kepatuhan konsumsi TTD pada remaja putri masih rendah akibat berbagai hambatan, baik fisik, psikologis, maupun sosial. Pemahaman mendalam mengenai pengalaman remaja putri dalam mengonsumsi TTD diperlukan untuk meningkatkan efektivitas program pencegahan anemia. Tujuan: Untuk mengeksplorasi pengalaman hidup remaja putri dalam mengonsumsi tablet tambah darah (TTD). Metode: Studi kualitatif menggunakan pendekatan fenomenologi deskriptif. Penelitian ini dilakukan di SMP Negeri 5 Cikarang Utara, Kabupaten Bekasi, Jawa Barat, pada tanggal 16 Juni hingga 15 Agustus 2025. Partisipan berjumlah 8 remaja putri berusia 13–15 tahun yang dipilih secara purposive sampling. Pengumpulan data dilakukan melalui wawancara mendalam yang berlangsung selama 30–50 menit dan dianalisis menggunakan metode Colaizzi. Hasil: Analisis data menghasilkan tiga tema utama, yaitu: (1) hambatan dan kendala dalam konsumsi TTD yang meliputi rasa tablet yang tidak nyaman, efek samping fisik, serta ketidakdisiplinan dan lupa; (2) persepsi positif dan manfaat konsumsi TTD yang mencakup peningkatan pemahaman serta perubahan fisik dan energi tubuh; dan (3) dukungan eksternal dan strategi meningkatkan kepatuhan yang melibatkan peran guru, teman sebaya, keluarga, serta strategi pribadi remaja dalam mengatasi hambatan. Simpulan: Pengalaman remaja putri dalam mengonsumsi TTD dipengaruhi oleh interaksi antara hambatan fisik, persepsi manfaat, dan dukungan lingkungan. Keberhasilan program TTD tidak hanya bergantung pada distribusi tablet, tetapi juga pada edukasi berkelanjutan, dukungan sosial, dan strategi implementasi yang sesuai dengan karakteristik remaja putri. Saran: Penelitian selanjutnya disarankan untuk mengatasi keterbatasan studi ini dengan menggunakan desain kuantitatif atau metode campuran untuk meneliti hubungan antara kepatuhan terhadap konsumsi tablet tambah darah dan indikator anemia objektif, seperti kadar hemoglobin, di kalangan remaja putri. Kata Kunci: Anemia; Remaja Putri, Tablet Tambah Darah (TTD).